Manufacturing method for lithium metal phosphate (LMP) cathode material
A cost-effective and scalable method for synthesizing lithium iron phosphate cathode materials using lower-cost raw materials and controlled carbon content addresses the inefficiencies of existing methods, resulting in improved electrochemical performance and reduced impurities.
Patent Information
- Application Number
- JP2024541664
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-21
- Filing Date
- 2023-01-20
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for synthesizing lithium iron phosphate (LFP) cathode materials are costly, time-consuming, and prone to forming undesirable impurities due to high-pressure hydrothermal processes and solid-state methods, which also require expensive lithium sources and complex recycling.
A method using lower-cost raw materials and minimal processing, involving the reaction of a metal source, phosphate-containing acid, and organic acid in a solvent, followed by lithium addition, precipitate formation, drying, and calcination, to produce lithium iron phosphate with a carbon coating, optimizing carbon content between 1-3% by weight for improved conductivity.
The method achieves uniform particle distribution, reduced impurities, and enhanced electrochemical performance, making it suitable for lithium-ion batteries with cost-effective and scalable production.
Smart Images

Figure 2025502168000004 
Figure 2025502168000005 
Figure 2025502168000006
Abstract
Description
[Technical field]
[0001] The present invention relates to lithium metal phosphate LiMPO4 (LMP) cathode materials, where M represents Fe, Mn, Ni or Co and combinations thereof. The present invention also relates to improved methods for the synthesis of LMPs. More specifically, the present invention relates to the synthesis of a particularly preferred LMP, which is the cathode material LiFePO4 (LFP), from low-cost materials. Even more preferably, the present invention relates to an improved synthesis of LMPs, especially LFPs, which preferably contain carbon as a coating.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to pending U.S. Provisional Patent Application No. 63 / 301,767, filed January 21, 2022, and is incorporated herein by reference. [Background technology]
[0003] LMP, more specifically LFP, is a widely used cathode material for lithium-ion batteries. LFP is commercially synthesized by either solid-state or hydrothermal processes, both of which require multiple time-consuming steps or expensive precursors. Both solid-state and hydrothermal processes are known to form undesirable impurities. The final cathode material is typically coated with a carbon source to increase the electrical conductivity, thereby forming a material referred to in the art as LiFePO4 / C, which stands for carbon-coated lithium iron phosphate, with the understanding that the carbon stoichiometry is not represented by the abbreviated designation LiFePO4 / C or the corresponding designation LFP / C. For purposes of this disclosure, the designation LMP / C is a similar designation that refers to LiMPO4 / C, which is a carbon-coated lithium metal phosphate.
[0004] Solid-state processes require homogenous mixtures with uniform particle distribution, which is difficult to achieve on a manufacturing scale. Mechanical mixing and grinding of large amounts of solids at high temperatures is a difficult process to control in an industrial environment that results in the formation of undesirable impurities.
[0005] The hydrothermal process requires excess LiOH and produces Li2SO4 waste as a by-product. Lithium hydroxide is a relatively expensive source of lithium, and Li2SO4 is an undesirable by-product that requires recycling. The need to recycle Li2SO4 complicates and increases costs in the overall manufacturing process. The hydrothermal process also requires the use of high pressure autoclave reactors at high temperatures, which is an expensive process at high volumes.
[0006] Despite the difficulties associated with synthesis, LFP remains widely accepted worldwide as a preferred cathode material for batteries. Growth is expected in lithium-ion batteries, especially LFP cathodes. Due to the ongoing awareness of the environmental impact of the manufacturing process and the costs and difficulties associated with the synthesis of LFP, those skilled in the art have had a long-standing need for a synthesis method that can use lower-cost raw materials and requires less processing. An improved synthesis method is provided herein. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention relates to an improved method for producing cathode materials comprising lithium metal phosphates, preferably further comprising carbon as a coating, and more particularly, lithium iron phosphate, preferably comprising carbon as a coating.
[0008] More specifically, the present invention relates to a method for the synthesis of lithium iron phosphate / carbon (LFP / C) materials that uses lower cost raw materials or starting materials. The problem is that it is not possible to visually confirm the input position. [Means for solving the problem]
[0009] A particular feature of the present invention is the production of LiFePO4 / C from a source containing zero-valent iron, such as elemental iron or steel.
[0010] These and other embodiments, as realized, are provided in a process for forming a lithium metal phosphate cathode material. The method includes forming a lithium metal phosphate cathode material, the method including the steps of: reacting a metal source, a phosphate-containing acid and an organic acid in a solvent to form a metal phosphate; Addition of a lithium source to the solvent; causing a precipitate to form; drying the precipitate; and calcining the precipitate; Thereby forming a lithium iron phosphate cathode material, said lithium iron phosphate cathode material containing up to 3% by weight carbon.
[0011] Yet another embodiment is provided in a process for forming a lithium metal phosphate cathode material comprising the steps of: reacting a metal source, phosphoric acid and an organic acid in a solvent to form a metal phosphate; Addition of a lithium source to the solvent; causing a precipitate to form; drying the precipitate; and calcining the precipitate; Thereby forming a lithium iron phosphate cathode material, said lithium iron phosphate cathode material containing up to 3% by weight carbon. [Brief description of the drawings]
[0012] [Figure 1]FIG. 1 is an x-ray diffraction (XRD) pattern of the precursor material.
[0013] [Diagram 2] FIG. 2 is the XRD pattern of the fired material.
[0014] [Diagram 3] FIG. 3 is a graphical representation of the rate capability test in a half-cell from C / 10 to 10C.
[0015] [Figure 4] FIG. 4 is a graphical representation of 1C cycling on a half-cell up to 100 cycles.
[0016] [Diagram 5] FIG. 5 is a graphical representation of the first charge / discharge voltage profile of the half-cell at a C / 10 rate.
[0017] [Figure 6] FIG. 6 is a graphical representation of a typical firing profile. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention relates to an improved synthesis of LMP / C, more specifically LiFePO4 / C, that utilizes lower cost raw materials and minimal processing. More specifically, the present invention relates to a method for forming LiFePO4 / C directly from iron or an iron-containing alloy, such as steel, using elemental metal or metal in the zero oxidation state.
[0019] The method for synthesizing LiMPO4 preferably utilizes the reaction of a phosphate containing acid and an organic acid with a metal source in a solvent, most preferably water, to form a metal phosphate, preferably iron phosphate. A lithium source, such as lithium carbonate or lithium hydroxide, is then added, followed by drying and calcination. The organic acid provides carbon, thereby forming LMPO4 / C, preferably LiFePO4 / C, which is a cathode material particularly suitable for lithium ion batteries.
[0020] Methods are described herein for the formation of lithium iron phosphate with the understanding that, for convenience, iron may be replaced on an equimolar basis with nickel, manganese, cobalt, or combinations thereof to achieve an olivine lithium metal phosphate, preferably including carbon as a coating, by the same methods, where the lithium metal phosphate or LFP has the general formula: Life x Ni a Mn y Co z PO4 where x + a + y + z = 1, During the ceremony: 0≦x≦1, more preferably 0.5≦x≦1, and most preferably 0.9≦x≦1; 0 < y ≦ 1, more preferably 0 ≦ y ≦ 0.5; 0 < z ≦ 1, more preferably 0 ≦ z ≦ 0.5; and 0 < a ≦ 0.1.
[0021] Suitable as a coating, carbon is desirable to obtain good electrochemical performance such as electrical conductivity, tap density, lithium ion diffusion, optimal particle size and phase purity. Carbon content also controls the crystal growth of LMP during sintering, and particle size is inversely correlated with carbon content. Tap density also inversely correlates with carbon content. Furthermore, at high carbon content, impurities appear due to iron reduction. If carbon content is insufficient, impurities are formed due to iron oxidation. A final carbon content of at least 1% by weight and no more than 3% by weight in LMPO4 / C is preferred to achieve optimal electrical conductivity with sufficient tap density and particle size. Most preferably, the carbon content in LMPO4 / C is at least 1.3% by weight to 2.5% by weight, and most preferably 1.4 to 1.7% by weight. When the carbon content in LMPO4 / C exceeds about 2 wt%, electrical conductivity is not appreciably improved and lithium ion diffusion rates may be impaired as the carbon coating thickness increases. For these reasons, and in order to maximize tap density, it is preferred to limit the carbon content in LMPO4 / C to about 2 wt% or less, more preferably to about 1.7 wt% or less.
[0022] The synthesis method includes the following steps: A metal source, preferably including iron, is combined with a phosphate-containing acid, preferably an aqueous solution including phosphoric acid. It is preferred to react in water, and thus a 40 wt% phosphoric acid solution can be used without being limited thereto. It is preferred to minimize water to minimize the amount of water removed during drying. An organic acid is preferably added before, after, or together with the phosphoric acid, with citric acid or oxalic acid being preferred. The reaction product of the metal source, phosphate-containing acid, and organic acid is a metal phosphate. With iron as the preferred metal, the iron is primarily, most preferably exclusively, in the +2 oxidation state.
[0023] The metal source may be an elemental metal, particularly elemental iron, or an alloy containing a zero-valent metal such as steel.
[0024] In another embodiment, the metal source is reacted with oxalic acid followed by the addition of a phosphate-containing acid, such as phosphoric acid, to form the metal phosphate.
[0025] The phosphate-containing acid is preferably phosphoric acid or a phosphoric acid ester represented by the formula: [ka] During the ceremony: R 1 ~R 6 Each of the groups is H and -PO(OR 7 )2, where each R 7 is independently selected from H, a substituted or unsubstituted alkyl of 1 to 20 carbons, a substituted or unsubstituted aryl of 6 to 20 carbons, or an alkylaryl of 7 to 21 carbons; However, R 1 ~R 6 At least one of is -PO(OH)2. Preferably, R 1 ~R 6 At least two of the groups are -PO(OH)2. More preferably, R 1 ~R 6 At least three of the groups are -PO(OH)2. More preferably, R 1 ~R 6 At least four of the groups are -PO(OH)2. More preferably, R 1 ~R 6 At least five of the groups are -PO(OH)2. Most preferably, R 1 ~R 6 is -PO(OH)2, where the phosphate ester is particularly preferably phytic acid. R 7 can be unsubstituted alkyl, aryl, or alkylaryl, or R 7 may be an alkali metal, preferably selected from lithium, sodium and potassium, and is preferably lithium.
[0026] A lithium source is added to the metal phosphate, the preferred lithium source being lithium carbonate or lithium hydroxide.
[0027] The metals, particularly iron, are maintained in the +2 oxidation state, preferably the metal iron phosphate is at least 50% by weight Fe3(PO4)2, more preferably at least 75% by weight Fe3(PO4)2, and most preferably at least 90% by weight Fe3(PO4)2.
[0028] At low temperatures below about 90°C, the formation of iron phosphate, such as Fe +3It is preferred to utilize conditions that inhibit the formation of , or, preferably for cost considerations, a non-oxidizing atmosphere (also called an inert atmosphere) containing low levels of oxygen, such as inert gas with nitrogen.
[0029] When oxalic acid is used, the metal forms an oxalate such as iron oxalate. 2+ Fe 3+ It is preferred to utilize a reducing acid such as citric acid to mitigate the oxidation to . When oxalic acid is used in combination with citric acid, reaction temperatures above about 60° C. are particularly preferred.
[0030] Particularly preferred carbon sources are organic acids, preferably carboxylic acids, particularly preferably di- or tricarboxylic acids. Di- and tricarboxylic acids having less than about 10, preferably alkyl, carbon atoms are most preferred. Particularly preferred acids are selected from the group consisting of citric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, isocitric acid, aconitic acid, propane-1,2,3-tricarboxylic acid and sucrose. Citric acid and oxalic acid are preferred due to their low cost and wide availability. Particularly suitable carbon sources include oxalic acid, citric acid or polyvinyl acid, with oxalic acid or a "mixture of citric and oxalic acids" being particularly suitable. Oxalic acid improves the handling properties of the reaction slurry. Reactions without oxalic acid tend to have insufficient carbon after firing. Reaction slurries without oxalic acid become thick and viscous when heated on a hot plate, as shown in the photo to the right, which relates to the ease of drying of the material. Polyvinyl alcohol is also a suitable carbon source.
[0031] The organic acid is preferably citric acid monohydrate (C6H8O7-H2O), and oxalic acid dihydrate (H2C2O4-2H2O) is particularly preferred.
[0032] A particularly suitable drying method for demonstration of the present invention incorporates a heated drum dryer comprising a heated drum, preferably an internally heated drum, with an alternative heat source such as infrared, laser heat, or UV heaters on the exterior of the drum. The alternative heat source spots heat materials on the opposite surface of the drum to change properties or cause a reaction in the dryness of a particular material.
[0033] Thin film drying can be accomplished as a batch process by drying the product with conduction from a surface at temperatures of about 150-250 °C. The material remains fixed to the surface for about 1 ms to several seconds before being scraped off the surface. This allows the material to become crystalline and not become sticky after drying. In this process, additional water of hydration is removed and some partial reactions such as oxalate decomposition and iron phosphate allotrope conversion can occur. Drum drying is a continuous variation of thin film drying with similar behavior.
[0034] Evaporative drying in trays results in similar behavior to the thin film drying method. The slurry is dried in a beaker-top reactor with mixing at about 90°C until it becomes "mudgy", and then the mud is transferred to a dry convection oven and processed at about 90°C overnight. The crystallinity is similar to thin film drying based on X-ray diffraction (XRD) and the product behavior has similar electrochemical properties. This low temperature crystallinity indicates that crystallinity forms over time at temperatures of about 90°C.
[0035] Spray drying in a dry air atmosphere at a relatively low temperature results in a powder material. Without being bound by theory, it is hypothesized that the mixture can remain below the glass transition temperature Tg of some of the components of the suitable powder. Inlet temperatures of about 150-180°C and outlet temperatures of about 110-130°C are suitable for demonstration of the present invention.
[0036] A dried powder containing a metal phosphate, a lithium source, and a carbon source is calcined to obtain LMP / C, preferably LiFePO4 / C. Calcination temperatures of 580-700°C under inert gas (also called inert atmosphere) are preferred. Above about 740°C, Fe3P impurity has been observed. Calcination at about 600°C, preferably for 1-10 hours, optionally with N 2(g) Firing or calcining of the powder under is exemplified to demonstrate the invention. Below about 1 hour, calcination may be incomplete. Above about 10 hours, the phosphate begins to decompose. Calcination times of about 4 hours to about 10 hours are preferred. The inert gas preferably contains less than 0.01% by weight of oxygen.
[0037] Lithium oxalate decomposes in the range of 556-585° C., with some decomposition to Li2CO3. By converting Li2CO3 to lithium oxalate, the decomposition can be carried out in the temperature range where the LFP is calcined in the preferred range of 580-700° C. Fe in the LFP is likely to catalyze the decomposition of Li2CO3 and lithium oxalate even in this temperature window.
[0038] Lower temperature firing, such as about 600°C, may allow the use of metal rotary kilns instead of roller hearths with saggars without resulting in metal contamination of the product, and may result in better product quality due to increased gas exposure to the powder. o C, may allow a metal rotary kiln to be used instead of roller hearth with saggars without resulting in metal contamination of product and better product quality due to an increase in gas exposure to the powder.).
[0039] Optimum firing is at 580-700°C for 4-10 hours. Firing time is a more important parameter than temperature in determining production cost, which is the limiting factor in furnace throughput.
[0040] Decomposition products do not necessarily need to be monitored since the primary decomposition products are gases at the calcination temperature. Expected decomposition products include CO2, CO, and H2O.
[0041] The primary particle sizes achieved by synthesis are typically around 200-400 nm in diameter, with a fairly uniform particle size distribution.
[0042] Ball milling is not preferred because it compacts some of the particles and results in a very polydisperse particle size distribution. Ball milling also results in high surface area material that is typically undesirable in the final lithium ion battery product, but which may be useful in other applications such as capacitors.
[0043] Wet bead milling with moderate energy input and short residence times is particularly preferred for producing high quality LFP. Wet milling with 1-1.2 mm zirconia beads with residence times of about 5-10 min / kg is suitable for demonstration of the present invention.
[0044] Tip speeds can be as low as 10-15 m / s, which is lower than typically used for this type of operation, and is thereby more energy efficient than operation at higher tip speeds. A slow tip speed also reduces wear and tear on the beads and machinery. A slow tip speed also reduces product contamination due to bead breakage. Tip speeds in wet bead mills remain fairly constant as the wet bead mill is scaled up to commercial scale units.
[0045] It is preferred to rotate the powder during firing or calcination. Firing the material in a saggar creates a gradient of material quality through the saggar, as each unit volume of the saggar experiences different temperature and atmosphere results during the firing cycle. This results in material with suboptimal average performance. Large differences in carbon content are observed between the top, middle, and bottom of the saggar, especially in deep saggar loads. To produce a uniform high quality material, the ideal firing method includes a method of agitating the material as it is fired. This can be accomplished practically in a rotary kiln or in a rotating ceramic or metal capsule with open ends and a geometry to contain the material as it rotates in the kiln.
[0046] The calcined powder can be segmented by size, such as by use of a sieve, or by jet milling if desired.
[0047] In comparison to the sager fired material, similar electrochemical capacity is obtained with the rotary capsule fired material. The capsule was found to have more uniform properties and it is theoretically expected that the capsule material will achieve higher overall performance when fired optimally.
[0048] The reaction of the iron salt with the phosphate can be carried out in an inert gas (also called an inert atmosphere) to prevent oxidation of Fe(II). For the purposes of this invention, an inert gas is defined as a gas that does not oxidize Fe(II). Suitable gases include, but are not limited to, N2 and the noble gases. N2 is 、 Oxygen, preferably less than 0.01% by weight, is particularly preferred due to its relatively low cost and widespread availability.
[0049] Throughout this specification, stoichiometric amount refers to the addition of reactants in amounts sufficient to form a product with the appropriate stoichiometry within experimental error. Stoichiometric amount as defined herein is within at least 5 mol% of the theoretical stoichiometric equivalent desired, preferably within 1 mol% of the theoretical stoichiometric amount desired. By way of example, stoichiometric equivalent amounts of lithium and phosphate preferably have a lithium to phosphate molar ratio of 0.95:1 to 1.05:1, preferably 0.99:1 to 1.01:1.
[0050] This process is readily scalable for large scale manufacturing using currently available equipment and / or innovations in this industry equipment. The cathode of the present invention is incorporated into a battery, which includes an anode, not limited herein, a separator, not limited herein, and a dielectric, not limited herein. The formation of a battery from the cathode, anode, separator, and dielectric of the present invention described herein is well known to those skilled in the art and further details are not necessary herein. EXAMPLES
[0051] The precursor to LiFePO4 / C was prepared by adding 28.00 g of zero-valent iron metal powder to 196 g of a 25 wt% solution of H3PO4 in deionized water. The mixture was stirred with an overhead mixer in a 2 L glass jacketed reactor at 20 °C. 15 min after the addition of the iron metal powder, 12.61 g of H2C2O4·2H2O was added, and 20 min after the addition of the iron metal powder, 24.01 g of C6H8O7 was added. In a separate beaker, 19.03 g of Li2CO3 was added to 250 mL of deionized water to form a suspension. This suspension was pump dropwise into the solution in the jacketed reactor at an addition rate of 0.38 g Li2CO3 / min, starting 45 minutes after the addition of the iron metal powder. The solution was then heated to 80° C. in the jacketed reactor and allowed to react for 22 hours. The final mixture was pumped out and spray dried to obtain a precursor powder. 9 g of the precursor powder was calcined in a sagger in a quartz tube furnace under N2 atmosphere with a N2 flow rate of 100 cc / min. The temperature was ramped to 100°C with a hold time of 30 minutes, and then to 600°C with a hold time of 8 hours. A ramp rate of 5°C / min was used throughout the calcination process. XRD of the precursor material presented as a hydrate is shown in Figure 1. XRD of the calcined material is shown in Figure 2. Figure 3 shows the rate capability tested in half-cells from C / 10 to 10. Figure 4 provides 1C cycling in half-cells up to 100 cycles, with error bars representing standard deviation of three cells. Figure 5 shows the first charge / discharge voltage profile in the half-cell at C / 10 rate. A graphical representation of the calcination temperature as a function of time is shown in Figure 6. Table 1: Summary of physical properties [Table 1]
Claims
1. A method for forming a lithium metal phosphate cathode material, comprising: reacting a metal source, a phosphate containing acid, and an organic acid in a solvent to form a metal phosphate; adding a lithium source to the solvent; forming a precipitate; and drying the precipitate; and calcining the precipitate, thereby forming a lithium iron phosphate cathode material; wherein the lithium iron phosphate cathode material comprises up to 3 weight percent carbon.
2. 2. The method for forming a lithium metal phosphate cathode material of claim 1 wherein the metal source comprises a zero valent metal.
3. 3. The method for forming a lithium metal phosphate cathode material of claim 2, wherein the zero valent metal is selected from the group consisting of Fe, Mn, Ni, and Co.
4. 2. The method for forming a lithium metal phosphate cathode material of claim 1 , wherein the metal source comprises elemental iron or an alloy containing iron.
5. 2. The method for forming a lithium metal phosphate cathode material as defined in claim 1 wherein the iron containing alloy is steel.
6. 2. The method for forming a lithium metal phosphate cathode material of claim 1 wherein the phosphate-containing acid is selected from the group consisting of phosphoric acid and phosphate esters.
7. 7. The method of forming a lithium metal phosphate cathode material of claim 6, wherein the phosphate-containing acid is phosphoric acid.
8. 7. The method of forming a lithium metal phosphate cathode material of claim 6, wherein the phosphate-containing acid is a phosphoric acid ester having the formula: 【Chemistry 1】 During the ceremony: R 1 ~R 6 Each of the groups is H and -PO(OR 7 ) 2 where each R 7 is independently selected from H, a substituted or unsubstituted alkyl of 1 to 20 carbons, a substituted or unsubstituted aryl of 6 to 20 carbons, or an alkylaryl of 7 to 21 carbons; However, R 1 ~R 6 At least one of the following is -PO(OH) 2 It is.
9. R 1 ~R 6 At least two of the following are -PO(OH) 2 9. The method of forming the lithium metal phosphate cathode material of claim 8,
10. R 1 ~R 6 At least three of the following are -PO(OH) 2 10. The method of forming the lithium metal phosphate cathode material of claim 9, wherein
11. R 1 ~R 6 At least four of the following are -PO(OH) 2 11. The method of forming the lithium metal phosphate cathode material of claim 10,
12. R 1 ~R 6 At least five of the following are -PO(OH) 2 12. The method of forming the lithium metal phosphate cathode material of claim 11,
13. 8. The method of forming a lithium metal phosphate cathode material of claim 7, wherein the phosphate ester is phytic acid.
14. R 7 is unsubstituted alkyl, aryl, or alkylaryl, or R 7 9. The method for forming a lithium metal phosphate cathode material of claim 8, wherein is lithium.
15. 2. The method of forming a lithium metal phosphate cathode material according to claim 1 , wherein the solvent is water.
16. 2. The method for forming a lithium metal phosphate cathode material of claim 1 wherein the organic acid comprises at least one carboxyl group.
17. 2. The method for forming a lithium metal phosphate cathode material of claim 1, wherein the organic acid is selected from the group consisting of citric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, citric acid, isocitric acid, aconitic acid, propane-1,2,3-tricarboxylic acid, sucrose, and polyvinyl acid.
18. 18. The method for forming a lithium metal phosphate cathode material of claim 17, wherein the organic acid is selected from the group consisting of oxalic acid and citric acid.
19. 2. The method for forming a lithium metal phosphate cathode material of claim 1 wherein the organic acid is oxalic acid, and the oxalic acid is reacted with the metal source prior to the addition of the phosphate-containing acid.
20. 20. The method for forming a lithium metal phosphate cathode material of claim 19 further comprising the addition of citric acid.
21. 21. The method of claim 20, wherein the reaction is carried out at a temperature of at least 60°C.
22. 2. The method of claim 1, wherein the reaction is carried out in an inert atmosphere.
23. 10. The method for forming a lithium metal phosphate cathode material of claim 1 , wherein the reaction is not in an inert atmosphere.
24. 2. The method of claim 1, wherein the lithium iron phosphate cathode material has the formula: LiFe x Ni a Mr y Co z NIGHT 4 where x + a + y + z = 1, During the ceremony: 0 ≦ x ≦ 1; 0 < y ≦ 1; 0 < z ≤ 1; and 0 < a ≦ 0.
1.
25. 25. The method for forming a lithium metal phosphate cathode material of claim 24, wherein x is 0.5≦x≦1.
26. 26. The method for forming a lithium metal phosphate cathode material of claim 25, wherein x is 0.9≦x≦1.
27. 25. The method for forming a lithium metal phosphate cathode material of claim 24, wherein y is 0≦y≦0.
5.
28. 25. The method for forming a lithium metal phosphate cathode material of claim 24, wherein z is 0≦z≦0.
5.
29. 10. The method for forming a lithium metal phosphate cathode material of claim 1 wherein the carbon is a coating.
30. 13. The method for forming a lithium metal phosphate cathode material of claim 1 comprising at least 1 weight percent carbon.
31. 31. The method for forming a lithium metal phosphate cathode material of claim 30 comprising up to 2.5 wt.% carbon.
32. 32. The method for forming a lithium metal phosphate cathode material of claim 31 comprising 1.4 to 1.7 weight percent carbon.
33. 10. The method for forming a lithium metal phosphate cathode material of claim 1, wherein the drying is selected from thin film drying and evaporative drying.
34. 34. The method for forming a lithium metal phosphate cathode material of claim 33, wherein the evaporative drying comprises spray drying at an inlet temperature of 150°C to 180°C.
35. 34. The method for forming a lithium metal phosphate cathode material of claim 33, wherein the thin film drying comprises drying in a drum dryer comprising a heated drum and an alternative heat source external to the drum.
36. 36. The method for forming a lithium metal phosphate cathode material of claim 35, wherein the alternative heat source is selected from infrared, laser heat, and UV heat.
37. 2. The method for producing a lithium metal phosphate cathode material according to claim 1, wherein the calcination is carried out at a temperature of 580°C to 700°C.
38. 2. The method for forming a lithium metal phosphate cathode material of claim 1 , wherein said calcining comprises tumbling said powder during said drying.
39. 10. The method for forming a lithium metal phosphate cathode material of claim 1 further comprising wet-grinding the precipitate prior to said drying.
40. 40. The method for forming a lithium metal phosphate cathode material of claim 39, wherein the wet-milling comprises milling with 1-1.2 mm zirconia beads at a tip speed of about 10-15 m / s with a residence time of about 5-10 min / kg.
41. reacting a metal source, phosphoric acid and an organic acid in a solvent to form a metal phosphate; adding a lithium source to the solvent; forming a precipitate; and drying the precipitate; and calcining the precipitate, thereby forming the lithium iron phosphate cathode material, wherein the lithium iron phosphate cathode material contains up to 3 wt.% carbon; 1. A method for forming a lithium metal phosphate cathode material comprising:
42. 42. The method for forming a lithium metal phosphate cathode material of claim 41 wherein the metal source comprises a zero valent metal.
43. 43. The method for forming a lithium metal phosphate cathode material of claim 42, wherein the zero valent metal is selected from the group consisting of Fe, Mn, Ni, and Co.
44. 42. The method for forming a lithium metal phosphate cathode material of claim 41 , wherein the metal source comprises elemental iron or an alloy containing iron.
45. 42. The method for forming a lithium metal phosphate cathode material of claim 41 wherein the alloy including iron is steel.
46. 42. The method for forming a lithium metal phosphate cathode material of claim 41 , wherein the solvent is water.
47. 42. The method for forming a lithium metal phosphate cathode material of claim 41 wherein the organic acid comprises at least one carboxyl group.
48. 42. The method for forming a lithium metal phosphate cathode material of claim 41, wherein the organic acid is selected from the group consisting of citric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, citric acid, isocitric acid, aconitic acid, propane-1,2,3-tricarboxylic acid, sucrose, and polyvinyl acid.
49. 49. The method for forming a lithium metal phosphate cathode material of claim 48, wherein the organic acid is selected from the group consisting of oxalic acid and citric acid.
50. 42. The method for forming a lithium metal phosphate cathode material of claim 41 wherein the organic acid is oxalic acid and the oxalic acid is reacted with the metal source prior to the addition of the phosphate-containing acid.
51. 51. The method for forming a lithium metal phosphate cathode material of claim 50 further comprising the addition of citric acid.
52. 52. The method of forming a lithium metal phosphate cathode material as set forth in claim 51, wherein the reaction is conducted at a temperature of at least 60°C.
53. 42. The method of forming a lithium metal phosphate cathode material as set forth in claim 41, wherein the reacting is carried out in an inert atmosphere.
54. 42. The method for forming a lithium metal phosphate cathode material of claim 41, wherein the reacting is not in an inert atmosphere.
55. 42. The method for forming a lithium metal phosphate cathode material of claim 41, wherein the lithium iron phosphate cathode material has the formula: LiFe x Ni a Mr y Co z NIGHT 4 where x + a + y + z = 1, During the ceremony: 0 ≦ x ≦ 1; 0 < y ≦ 1; 0 < z ≤ 1; and 0 < a ≦ 0.
1.
56. 56. The method for forming a lithium metal phosphate cathode material of claim 55, wherein x is 0.5≦x≦1.
57. 57. The method for forming a lithium metal phosphate cathode material of claim 56, wherein x is 0.9≦x≦1.
58. 56. The method for forming a lithium metal phosphate cathode material of claim 55, wherein y is 0≦y≦0.
5.
59. 57. The method for forming a lithium metal phosphate cathode material of claim 56, wherein z is 0≦z≦0.
5.
60. 42. The method for forming a lithium metal phosphate cathode material of claim 41 wherein the carbon is a coating.
61. 42. The method for forming a lithium metal phosphate cathode material of claim 41 comprising at least 1 wt.% carbon.
62. 62. The method for forming a lithium metal phosphate cathode material of claim 61 comprising up to 2.5 wt.% carbon.
63. 63. The method for forming a lithium metal phosphate cathode material of claim 62 comprising 1.4 to 1.7 weight percent carbon.
64. 42. The method for forming a lithium metal phosphate cathode material of claim 41, wherein the drying is selected from thin film drying and evaporative drying.
65. 65. The method for forming a lithium metal phosphate cathode material of claim 64, wherein the evaporative drying comprises spray drying at an inlet temperature of 150°C to 180°C.
66. 65. The method for forming a lithium metal phosphate cathode material of claim 64, wherein the thin film drying comprises drying in a drum dryer, the drum dryer comprising a heated drum and an alternative heat source external to the drum.
67. 67. The method for forming a lithium metal phosphate cathode material of claim 66, wherein the alternative heat source is selected from infrared, laser heat, and UV heat.
68. 42. The method of forming a lithium metal phosphate cathode material as claimed in claim 41, wherein the calcination is carried out at a temperature of from 580°C to 700°C.
69. 42. The method for forming a lithium metal phosphate cathode material of claim 41, wherein the calcining comprises tumbling the powder during the drying.
70. 42. The method for forming a lithium metal phosphate cathode material of claim 41 further comprising wet-grinding said precipitate prior to said drying.
71. 71. The method for forming a lithium metal phosphate cathode material of claim 70, wherein the wet-milling comprises milling with 1-1.2 mm zirconia beads at a tip speed of about 10-15 m / s with a residence time of about 5-10 min / kg.
Citation Information
Patent Citations
Preparation method of iron phosphate, iron phosphate prepared by method, preparation method of lithium iron phosphate, lithium iron phosphate prepared by method and lithium battery
CN107565132A
Iron phosphate and preparation method thereof
CN113942988A
Synthesis of lithium metal phosphate / carbon nanocomposites with phytic acid
EP2098483A1
Cathode material for manufacturing rechargeable battery
JP2007305585A
Method for preparing positive electrode material for secondary cell, and secondary cell
WO2004036671A1